Does a Virtual like Cause Actual Liking? How following a Brand's Facebook Updates Enhances Brand Evaluations and Purchase Intention. Issue 1 (November 2015) - Beukeboom, Camiel J.; Kerkhof, Peter; De Vries, Metten
Studies have shown positive associations between liking a Facebook brand page and brand evaluations, but causal evidence is lacking. This online pre–post-measure experiment compared brand evaluations of 'current followers' of a target brand's Facebook page, with 'new followers' instructed to 'like' the page, and 'non-followers' over one month. Results showed a significant positive increase for new followers on brand evaluations, whereas non-followers showed no change. Current followers were most positive in evaluations overall, but showed no change over time. This provides evidence that following a brand's Facebook updates can cause positive changes in brand evaluations. The effects were explained by perceived conversational human voice, indicating the importance of brand interactivity. Implications for brands' social media presence are discussed.